IMPLEMENTASI DAN OPTIMALISASI DAPODIK DI SMKN 4 PALOPO - DAMAYANTI, RISKA; PRATIWI, DWI NURAHMA; SANUSI, SOPNA AR (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2024)
The aim of this study is to analyze the implementation and optimization of the Education Base Data (Dapodik) in SMKN 4 Palopo. The method used was descriptive qualitative through observation, interviews, and documentation. Dapodik, as an educational information system developed by the Ministry of Education and Culture, manages national education data, including student data, teacher data, facilities and infrastructure, and other aspects. Although effectively implemented in SMKN 4 Palopo, there are technical and administrative constraints that need to be addressed. The main constraints include limited network infrastructure that slows down application access, lack of training for staff and teachers, and technical issues such as application bugs and software-hardware incompatibility. Data input errors also frequently occur, affecting the accuracy of reports and data-driven decision making. This study proposes several optimization steps, including regular training and workshops for administrative staff and teachers, hardware and software updates to ensure compatibility and optimal performance, network infrastructure improvements by strengthening internet connections and expanding Wi-Fi networks in school areas, and periodic data audits to ensure accuracy and consistency of input data. The implementation of these steps is expected to improve the efficiency and accuracy of educational data management at SMKN 4 Palopo, supporting better data management and more accurate decision-making. This study makes a significant contribution to understanding the constraints and solutions in the implementation of Dapodik. Keywords: Dapodik, Implementation, Educational Information System, SMKN 4 Palopo, Educational Data Management. ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi dan optimalisasi Data Pokok Pendidikan (Dapodik) di SMKN 4 Palopo. Metode yang digunakan adalah deskriptif kualitatif melalui observasi, wawancara, dan dokumentasi. Dapodik, sebagai sistem informasi pendidikan yang dikembangkan oleh Kementerian Pendidikan dan Kebudayaan, mengelola data pendidikan secara nasional, mencakup data siswa, guru, sarana prasarana, dan aspek lainnya. Meskipun diterapkan secara efektif di SMKN 4 Palopo, terdapat kendala teknis dan administratif yang perlu diatasi. Kendala utama termasuk keterbatasan infrastruktur jaringan yang memperlambat akses aplikasi, kurangnya pelatihan operator, serta masalah teknis seperti bug aplikasi dan ketidakcocokan perangkat lunak dengan perangkat keras. Kesalahan input data juga sering terjadi, mempengaruhi keakuratan laporan dan pengambilan keputusan berbasis data.Penelitian ini mengusulkan beberapa langkah optimalisasi, yaitu peningkatan pelatihan rutin dan workshop bagi operator, pemutakhiran perangkat keras dan lunak untuk memastikan kompatibilitas dan kinerja optimal, peningkatan infrastruktur jaringan dengan memperkuat koneksi internet dan memperluas jaringan Wi-Fi di area sekolah, serta audit data berkala untuk memastikan keakuratan dan konsistensi data yang diinput. Implementasi langkah-langkah ini diharapkan dapat meningkatkan efisiensi dan akurasi pengelolaan data pendidikan di SMKN 4 Palopo, mendukung pengelolaan data yang lebih baik dan pengambilan keputusan yang lebih tepat. Penelitian ini memberikan kontribusi penting dalam memahami kendala dan solusi dalam implementasi Dapondik.